2022
DOI: 10.1088/1674-1056/ac4a6d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of phase optimization of tapping mode atomic force microscope

Abstract: Phase image in tapping mode atomic force microscope (TM-AFM) results from various dissipation in microcantilever system. The phases mainly reflected the tip-sample contact dissipations which allowed the nanoscale characteristics to be distinguished. In this research investigation, two factors affecting the phase and phase contrast were analyzed. It was concluded from the theoretical and experimental results that the phases and phase contrasts in the TM-AFM were related to the excitation frequencies and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…where π‘š represents the equivalent mass of the microcantilever beam; 𝑐 represents the equivalent external damping that describes background dissipation; π‘˜ is the spring constant of the microcantilever beam; 𝑧 represents the absolute displacement of the tip; and 𝑧 represents the support excitation. A number of studies have now shown that the tip-sample contact stiffness is small and has little effect on the intrinsic frequency of the probe [5,16,17]. Therefore, the effect of π‘˜ can be neglected and Eq.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…where π‘š represents the equivalent mass of the microcantilever beam; 𝑐 represents the equivalent external damping that describes background dissipation; π‘˜ is the spring constant of the microcantilever beam; 𝑧 represents the absolute displacement of the tip; and 𝑧 represents the support excitation. A number of studies have now shown that the tip-sample contact stiffness is small and has little effect on the intrinsic frequency of the probe [5,16,17]. Therefore, the effect of π‘˜ can be neglected and Eq.…”
Section: Theoretical Modelmentioning
confidence: 99%